Solid-state 1H and 27Al NMR studies of DMSO-kaolinite intercalates - Fafard, Jonathan; Terskikh, Victor; Detellier, Christian (Université d'Ottawa | University of Ottawa, 2017)
Nuclear magnetic resonance (NMR) provides a powerful tool to describe local nuclear environments. In this work, unique structural information on kaolinite and on kaolinite dimethylsulfoxide (DMSO) intercalate were provided by solid-state 1H and 27Al magic-angle spinning (MAS) NMR. The interlayer chemistry of kaolinite (K) was examined by intercalating a select group of highly polar organic molecules or salts into kaolinite as a first step. Once the interlayer space is expanded, the intercalated compounds can be replaced in a second step. Intercalating DMSO into kaolinite to form the DMSO-K intercalate is, thus, a particularly useful first step toward the intercalation of a large variety of molecules, including polymers and ionic liquids. Well developed characterization methods are essential to define the structural modifications of kaolinite, and MAS NMR is a useful complement to other techniques. The use of 1H and 27Al MAS NMR for this purpose has been relatively rare. 1H NMR, nevertheless, can give unique information about kaolinite hydroxyls. Because quadrupolar interactions are sensitive to the local octahedral Al(III) geometry, solid-state 27Al NMR can follow subtle structural modifications in the octahedral sheet. In the present work, the 1H MAS NMR chemical shifts of KGa-1b were unambiguously attributed to the internal surface hydroxyls at 2.7 ppm and to the internal hydroxyls at 1.7 ppm. The 1H MAS NMR chemical shifts of the two methyl groups in DMSO-K are not equivalent and can be attributed to the 2.9 and 4.2 ppm peaks. The 27Al MAS NMR spectra of KGa-1b obtained under different magnetic fields revealed that most of the quadrupolar effects were highly reduced at 21.1 T, whereas the spectra at lower field, 4.7 T, were dominated by quadrupolar effects. The two octahedral Al(III) sites are not equivalent and can be distinguished in the low-field spectral simulation. Increased quadrupolar constants were observed and showed the major perturbations of the local Al symmetry that resulted from DMSO intercalation. Both the 1H and 27Al MAS NMR studies at different magnetic fields afforded important information about the local environments of the kaolinite hydroxyl groups and structural Al(III).
Keywords: 1H MAS NMR; 27Al MAS NMR; Deconvolution; DMSO; intercalation; kaolinite; clay minerals; quadrupolar interactions; solid-state NMR; chemical shifts